Evaluasi Pengolahan Air Limbah Domestik dengan IPAL Komunal di Kota Bogor - Susanthi, Dhama; Purwanto, Mohammad Yanuar; Suprihatin, Suprihatin (Jurnal Teknologi Lingkungan, 2018)
ABSTRACTOne of domestic wastewater treatment in Bogor City is by using communal WWTP (Wastewater Treatment Plant) system. The communal WWTP treats domestic wastewater with an anaerobic baffled reactor configuration (ABR). This study aims to determine the effluent quality of communal WWTP so that it can be used as reference for related institutions in managing communal WWTP. The effluent from 3 communal WWTPs namely KSM Amanah, Rosella, and Cipendek Indah measured the content of TSS, COD, oil and grease, ammonia, and total coliform. The secondary data of effluent from 40 communal WWTP were obtained from Environment Agency of Bogor City. The result of the effluent analysis is compared with the Minister of Environment and Forestry Regulation No. P.68/2016 on the Quality Standard of Domestic Wastewater. The study showed that the total coliform parameter did not meet the quality standard in 3 communal WWTP locations, COD exceeded the quality standard in KSM Rosella and Cipendek Indah, and TSS above the quality standard in KSM Cipendek Indah. The communal WWTP in Bogor city has not been effective in reducing the pollutant content in domestic wastewater especially BOD and total coliform. The communal WWTP management needs to be improved in order for better effluent.Keywords: domestic waste, communal WWTP, effluent, quality standard, bogor cityABSTRAKSalah satu pengolahan air limbah domestik di Kota Bogor yaitu menggunakan sistem IPAL komunal. IPAL komunal mengolah air limbah domestik dengan konfigurasi anaerobic baffled reactor (ABR). Penelitian ini bertujuan untuk mengetahui kualitas efluen IPAL komunal di Kota Bogor sehingga dapat dijadikan acuan bagi instansi terkait dalam mengelola IPAL komunal. Efluen dari 3 IPAL komunal yaitu KSM Amanah, Rosella, dan Cipendek Indah diukur kandungan TSS, COD, minyak lemak, amonia, dan total coliform. Data sekunder efluen dari 40 IPAL komunal diperoleh dari Dinas Lingkungan Hidup Kota Bogor. Hasil analisis efluen tersebut dibandingkan dengan baku mutu PermenLHK No. P.68/2016 tentang Baku Mutu Air Limbah Domestik. Penelitian menunjukkan bahwa parameter total coliform tidak memenuhi baku mutu di 3 lokasi IPAL komunal yang diteliti, COD melebihi baku mutu di KSM Rosella dan Cipendek Indah, serta TSS diatas baku mutu teridentifikasi di KSM Cipendek Indah. IPAL komunal di Kota Bogor belum efektif dalam menurunkan kandungan polutan dalam air limbah domestik terutama BOD dan total coliform. Pengelolaan IPAL komunal perlu ditingkatkan agar kualitas efluen yang dihasilkan lebih baik. Kata kunci: limbah domestik, IPAL komunal, efluen, baku mutu, kota bogor